Dampak Penggunanaan Smartphone Terhadap Hasil Belajar Siswa Sekolah Dasar - Zalmanidar Zalmanidar; Tengku Hafinda; Rahmat Saputra (Seutia Hukamaa Cendekia, 2024)
Misuse of smartphone devices can be detrimental to students, especially now that ownership is not limited by age, as even elementary school children have their smartphones, as do students at SD Negeri Tanjong Meulaboh, Kaway XVI District. This research aims to determine student learning achievement, the impact of smartphone device ownership on students, efforts by teachers to address the impact of smartphone ownership on student learning achievement, and the challenges teachers face in addressing the impact of smartphone ownership. This research uses a qualitative method with interview and documentation data collection techniques. The research data is analyzed using a qualitative descriptive method. The research results show that student learning achievement at SD Negeri Tanjong has decreased by an average percentage of 10.59%. Secondly, students' smartphone ownership significantly impacts student learning achievement and leads to moral degradation. Thirdly, teachers' efforts to address students' smartphone addiction include educating students about the dangers of excessive use, implementing specific school discipline related to smartphones by prohibiting students from bringing smartphones to school and confiscating them if found, and coordinating with parents. Lastly, the challenges faced by teachers in addressing the impact of smartphone ownership on student learning achievement include difficulties in managing students who use smartphone devices, as they tend to ignore teachers' instructions or advice, and challenges from parents who seem to allow their children to spend excessive time playing with their phones.